Ringing of the Regular Black Hole with Asymptotically Minkowski Core - Alexander Marcus Simpson (MDPI AG, 2021)
A Regge–Wheeler analysis is performed for a novel black hole mimicker ‘the regular black hole with asymptotically Minkowski core’, followed by an approximation of the permitted quasi-normal modes for propagating waveforms. A first-order WKB approximation is computed for spin zero and spin one perturbations of the candidate spacetime. Subsequently, numerical results analysing the respective fundamental modes are compiled for various values of the a parameter (which quantifies the distortion from Schwarzschild spacetime), and for various multipole numbers ℓ. Both electromagnetic spin one fluctuations and scalar spin zero fluctuations on the background spacetime are found to possess shorter-lived, higher-energy signals than their Schwarzschild counterparts for a specific range of interesting values of the a parameter. Comparison between these results and some analogous results for both the Bardeen and Hayward regular black holes is considered. Analysis as to what happens when one permits perturbations of the Regge–Wheeler potential itself is then conducted, first in full generality, before specialising to Schwarzschild spacetime. A general result is presented explicating the shift in quasi-normal modes under perturbation of the Regge–Wheeler potential.